Efektivitas Teknik Role Playing Dalam Layanan Konseling Kelompok Untuk Meningkatkan Komunikasi Interpersonal Siswa - Nurul Lailiyah; Muslim Afandi (Fakultas Tarbiyah dan Keguruan, 2020)
This research aimed at knowing the effectiveness of Role Playing technique on Group Counseling service in increasing student interpersonal communication. The problems at State Junior High School 4 Siak Hulu were the students who had low social interaction, whodaydreamed, who were closed, unconfident, and alone. Quantitative approach was used in this research by using pre-Experimental research with the on group Pretest-Posttest design. The object of this research was the effectiveness of using Role Playing technique on Group Counseling service in increasing student interpersonal communication The subjects of this research were students having low interpersonal communication and they were 10 students. Technique was used in this research.The techniques of collecting the data were questionnaire, observation, and documentation. The technique of analyzing the data was Wilcoxon’s Signed Ranks Test. The research findings showed that student social interaction before being given Role Playing in Group Counseling was on low category and the mean score was 65.5. After being given Role Playing technique on Group Counseling service in increasing student interpersonal communication increased to the high score and the mean score was 91.5. Based on the hypothesis test result using Wilcoxon test, it was obtained that the probability score 0.005 was lower than 0.05, it meant that Null hypothesis was rejected and Alternative hypothesis was accepted.